Introduction to the special issue: Images of the Olympic Games - Pierre-Olaf Schut; Marion Philippe (Universidad Politécnica de Madrid, 2024)
The Olympic Games are an exceptional global event; held every 4 years and receive exponential media coverage. The two weeks of competition are unforgettable, generating countless images of sporting achievements, host cities and sporting events. They create stories -some marvellous, others dramatic- around the athletes, but also events within the event. They create images and construct representations. The Olympic institution and the various stakeholders (sports organisations, sponsors, broadcasters, host territories, etc.) commit themselves to take over the production process of these representations and control them in order to ensure that their strategies/policies are implemented. Image is primarily controlled by the International Olympic Committee. The international sports institution exists through its image; it must control and sustain it (Giesen Hallmann 2018) to keep support from the public and therefore from the media as well as companies. Indeed, the Partners programme implemented in the 1980s and supported by Juan Antonio Samaranch, President of the IOC from 1980 to 2001, is based on the benefits that companies hope to gain from this partnership, which is primarily a matter of image (Stipp 1998). As Marc Lits (1997) explains, it is because of the way an event is portrayed by the media that it actually becomes an event. This makes it a godsend both for corporations, which can use it as a means of making money, and for athletes, as part of the commodification of sport and the Olympic Games that began in the 1980s. The question of image as iconography, but also as representation, is therefore central to the long-term future of an event like the Olympic Games. Of course, private and commercial issues are linked to public ones. The commitment of host cities and their country is largely driven by the desire to (re)build an appealing image. The attractiveness of the area for tourism or commercial activities is fundamental (Kenyon Bodet 2012; Hahm, Taci Terry 2018). The image issues raised by public actors are also symbolic and cultural. Opening ceremonies are the best examples to express the host country's history, culture and values (Hogan 2003; Kramavera Grix 2023). Minorities who make demands, whether peacefully or violently, also disrupt the Games to take advantage of the spotlight they represent. But national identity remains at the heart of the Games, as flags are raised, and anthems sung at the end of each event. These symbols are in many ways an extension of an international competition between countries defending their athletic performance in a globalised society. In this respect, the medals won by champions help to forge sporting identities and, by extension, national identities. Through the various articles in this issue, we intend to contribute to this vast and complex theme. We do not claim to exhaust the subject, but rather to shed light on some of its aspects. Through their diversity, the authors offer complementary perspectives on various Olympics, sports, and countries.